The Atualidades Project – a generator of improvement in the teaching-learning process: report of a teaching method carried out in a higher education institution - Orlandi, Orlandy; Junges, Ivone (Review of Business Management, 2015)
Objective – Being up-to-date requires reading newspapers and articles concerning issues that are relevant to professional training; the objective of this paper is to present the teaching method Atualidades project – a generator of improvement in the teaching-learning process, carried out in a higher education institution. Design/methodology/approach – This is qualitative, exploratory research, containing testimonies by 50 students, six invited entrepreneurs and professionals, and four teachers, between years 2006 and 2010, using direct observation of students’ and guests’ presentations, document analysis of project data, and testimonies by those involved. Analytical categories: recognizing the importance of updating, relationship between selected material and subject content, awakening to the interface between theory and practice, discovery of and access to a greater amount of research sources, sharing of ideas and improvement in capacity of working in the classroom. Theoretical framework – This study considered research on teaching and learning based on systematic, disciplined, reflective and meaningful reading and interpretation of knowledge produced worldwide, which requires professionals who are connected with the world through knowledge, constant appreciation of citizens and their local, regional and international actions, in which reading is considered a promoter of prosperity and social inclusion (Lowman, 2004; Dewey, 1978; Pestalozzi, 1946). Findings – The results revealed that students, when seeking to update themselves through reading, discovered local reference business practices. Contributions – The studied teaching method contributes to education concerning teaching and learning and corroborates studies that discuss the formation of critical minds in higher education.